REKAYASA SISTEM ABSENSI MAHASISWA BERBASIS RFID PADA PROGRAM STUDI TEKNIK ELEKTRO UNIVERSITAS UDAYANA - Mubaroq, Aditya Wahyu; Sita Purnamasari, Ni Kadek; Artha Mahesa, Kadek Rama; Sudarma, Made; Arsa Suyadnya, I Made; Care Khrisne, Duman (Jurnal SPEKTRUM; Vol 12 No 1 (2025): Jurnal SPEKTRUM, 2025)
Conventional attendance systems have shortcomings, such as inaccurate recording, waste of paper, and the need for storage space. Digital attendance technology, such as RFID-based, can overcome these shortcomings. This research develops RFID-based hardware by utilizing student identity cards (KTM) as RFID tags. Website-based backend as an RFID-based attendance system interface. The hardware design method uses the prototype method. The website-based backend was developed using the Software Development Life Cycle (SDLC) method. The database used to store data is developed using a relational model. The respondents of this research were students of the 2021 Electrical Engineering Study Program Concentration in Computer Engineering who were determined using the purposive sampling method. This research was tested using functionality testing, black box testing, and system performance testing. The implementation results show that the RFID-based attendance system has proven to be accurate, with 100% accuracy and an average attendance time of 3.6 seconds. The Laravel Filament backend and REST API run optimally, supporting card registration and real-time automatic attendance recording. This system reduces human error, speeds up attendance, and testing ensures all functions meet specifications with a user-friendly design.